Towards a formal study of automatic failure recovery in protocol-based web service composition. Issue 2 (June 2016) - Menadjelia, Nardjes
Abstract In the protocol-based Web service composition, the runtime unavailability of component services may result in a failed execution of the composite. In literature, multiple recovery heuristics have been proposed. This work provides a formal study and focuses on the complexity issues of the recovery problem in the protocol-based Web service composition. A recovery is a process responsible of migrating the failed execution into an alternative execution of the composite that still has the ability to reach a final state. The alternative execution is called a recovery execution. Following failure occurrence, several recovery executions may be available. The problem of finding the best recovery execution(s) is called the recovery problem. Several criteria may be used to determine the best recovery execution(s). In this work, we define the best recovery execution as the one which is attainable from the failed execution with a maximal number of invisible compensations with respect to the client. We assume that all transitions are compensatable. For a given recovery execution, we prove that the decision problem associated with computing the number of invisibly compensated transitions is NP-complete, and thus, we conclude that deciding of the best recovery execution is in $$Σ _2^P$$ Σ 2 P .